(untitled) (Progressive Agriculture, 2015)
An experiment was conducted at the Horticulture Farm of Bangladesh Agricultural University, Mymensingh to test the impact of plant growth regulators on growth and yield of summer tomato. The experiment consisted of two tomato varieties viz. BARI Hybrid Tomato-4 and BARI Hybrid Tomato-8 and four types of plant growth regulator (PGR)viz.,(i) control (without PGR), (ii) 4-CPA (4-chlorophenoxy acetic acid), GA3 (gibberellic acid) and 4-CPA +GA3. The two-factor experiment was laid out in randomized complete block design with three replications. The results of the experiment revealed that significant variations were observed for most of the characters studied. At 75 DAT, the tallest plant (79.35 cm), number of flowers and fruits (38.11 and 19.04, respectively) plant-1, individual weight (58.44 g) and fruit yield (22.75 t ha-1) were found in BARI Hybrid Tomato-8.At 75 DAT the maximum plant height (87.90 cm), number of flowers and fruits (49.04 and 21.9, respectively) plant-1, individual fruit weight (61.16 g), and fruit yield (27.28 tha-1) were found when 4-CPA + GA3 applied together, whereas the minimum for these characters were recorded from control plants. In case of combined effect of variety and plant growth regulator, the maximum plant height (87.90 cm), number of flowers and fruits (49.04 and 21.91, respectively) plant-1, individual fruit weight (61.16 g) and fruit yield (27.28 t ha-1) were observed in BARI Hybrid Tomato-8 when treated with 4-CPA + GA3together, and the minimum for all these parameters were found in control plants. The results of the present study suggest thatboth 4-CAP and GA3together can be practiced for increasing summer tomato production for both the varieties. Progressive Agriculture 26:32-37, 2015